Edukasi Pentingnya Menjaga Kesehatan Gigi Sejak Dini bagi Anak TK Dharma Wanita Tambakan - Ernata, Yusvidha; Mushofi, Yuskhil; Winarno, Winarno; Rohmah, Laila Nur (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
One of the often neglected aspects of body health is dental and oral health, which is commonly seen in young children. One of the issues is tooth decay, caused by inadequate dental and oral hygiene practices. This community service activity aims to educate students in Kindergarten (TK) about the importance of maintaining dental health from an early age, as well as to teach proper tooth brushing techniques and introduce foods that are healthy for the teeth. The activity was carried out at TK Dharma Wanita Gandusari, Blitar Regency, on September 1, 2025, with a total of 68 kindergarten children and 5 accompanying teachers. The methods used included interactive lectures, demonstrations, hands-on tooth brushing practice, and educational games. The results of the activity showed a significant increase in children's knowledge about dental health. This was evidenced by an average of 38% before the activity, which then increased to 88% after the activity. After this event, the children became more enthusiastic and started to get into the habit of brushing their teeth twice a day properly. This activity proved that a fun and interactive educational approach is very effective in instilling the habit of maintaining dental hygiene from an early age. Continuous support from teachers and parents is needed so that clean and healthy living behaviors, especially in maintaining dental health, can continue to be practiced by children both at home and at school.